2017
DOI: 10.1007/s10461-017-1777-7
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement: Supporting Safer Conception and Pregnancy For Men And Women Living with and Affected by HIV

Abstract: Safer conception interventions reduce HIV incidence while supporting the reproductive goals of people living with or affected by HIV. We developed a consensus statement to address demand, summarize science, identify information gaps, outline research and policy priorities, and advocate for safer conception services. This statement emerged from a process incorporating consultation from meetings, literature, and key stakeholders. Three co-authors developed an outline which was discussed and modified with co-auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 78 publications
(83 reference statements)
2
57
0
1
Order By: Relevance
“…In conclusion, this pilot of a comprehensive safer conception intervention effectively eliminated sexual HIV transmission and demonstrated high uptake of combination safer conception strategies, with preferences for strategies that are already available in public settings in sub-Saharan Africa. These findings reinforce international calls to scale-up programmatic delivery of safer conception services as a package intervention that promotes counselling on fertility desires and emphasizes the utility of ART, PrEP and timed condomless sex for safer conception [30]. Public health priorities include advancing the integration of safer conception counselling and services into existing healthcare programmes, engaging communities to promote acceptability of pregnancy among people affected by HIV, and expanding the number of service providers that are empowered to encourage discussion of pregnancy desires with HIV-affected individuals and couples.…”
Section: Discussionsupporting
confidence: 68%
“…In conclusion, this pilot of a comprehensive safer conception intervention effectively eliminated sexual HIV transmission and demonstrated high uptake of combination safer conception strategies, with preferences for strategies that are already available in public settings in sub-Saharan Africa. These findings reinforce international calls to scale-up programmatic delivery of safer conception services as a package intervention that promotes counselling on fertility desires and emphasizes the utility of ART, PrEP and timed condomless sex for safer conception [30]. Public health priorities include advancing the integration of safer conception counselling and services into existing healthcare programmes, engaging communities to promote acceptability of pregnancy among people affected by HIV, and expanding the number of service providers that are empowered to encourage discussion of pregnancy desires with HIV-affected individuals and couples.…”
Section: Discussionsupporting
confidence: 68%
“…While HIV affected couples were generally eager to learn more about safer conception [27, 36, 39, 44, 46, 48, 51, 54, 7274], there are numerous barriers to SCS access including stigma around HIV-affected couples wanting and bearing children [46]. Like our review, a recent consensus statement supporting safer conception and pregnancy for couples living with HIV found that access to SCS is limited by stigma toward HIV affected couples having children and that this stigma limits provision of safer conception services [75]. Increasing community education about SCSs via community health worker networks may help increase acceptability for previously unfamiliar conception strategies and reduce community-, provider-, or family-level stigma around pregnancy in HIV affected couples, as was accomplished with increasing community knowledge and acceptance of HIV testing [76, 77] and couples’ HIV counseling and testing [7880].…”
Section: Discussionmentioning
confidence: 96%
“…Serodiscordant couples face the unique challenge of minimizing the risk of HIV transmission to both the uninfected partner and any offspring . Nevertheless, many safer conception strategies currently exist that may be compatible with their fertility desires/intentions . One important strategy has been the uptake of antiretroviral therapy (ART) to suppress HIV viraemia.…”
Section: Introductionmentioning
confidence: 99%